An Error Analysis of Punctuation Use in Scientific Articles Written by Students of the Arabic Language Education Department at the State Islamic University of North Sumatra - Zikrani Khalilah; Zulheddi Zulheddi (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to analyze punctuation errors in Arabic-language academic articles written by students of the Arabic Language Education Study Program at Universitas Islam Negeri Sumatera Utara and published in Al-Ihya Journal edition 2025. The background of this research is the frequent occurrence of punctuation inaccuracies that affect the clarity and quality of academic writing. This study employs a descriptive qualitative approach using content analysis. The data consist of three articles written by 2021 cohort students, analyzed through documentation techniques including identification, classification, and interpretation of punctuation errors. The findings reveal 16 punctuation errors dominated by comma misuse (الفاصلة), followed by quotation marks, periods, colons, and parentheses. The types of errors identified include omission, addition, and inconsistency. These errors indicate that students still face difficulties in understanding the functions of punctuation within Arabic sentence structures. The study concludes that punctuation errors remain a significant issue in students’ academic writing and should receive greater attention in Arabic writing instruction.